Deciphering of differences in gut microbiota and plasma metabolites profile between non-obese and obese Golden Retrievers dogs - Cai, Yazhen; Tang, Huayu; Xiang, Guilin; Yi, Hongyu; Zhong, Jie; Xie, Zhaoxi; Hu, Qinfeng; El Bouhi, Romaissaa; Zhou, Pan; Zhang, Yong; Yan, Honglin (Frontiers in Microbiology, 2025)
IntroductionGolden Retrievers have a high risk of obesity, which is prevalent in dogs and is associated with inflammation and cancer, impairing the health and life expectancy of companion animals. Microbial and metabolite biomarkers have been proposed for identifying the presence of obesity in humans and rodents. However, the effects of obesity on the microbiome and metabolome of Golden Retrievers remains unknown. Therefore, this study was designed to evaluate the signatures of serum biochemistry indexes, gut microbiota and plasma metabolites in non-obese and obese Golden Retrievers, aiming to recognize potential biomarkers of canine obesity.MethodsA total of 8 non-obese (Ctrl group) and 8 obese (Obe group) Golden Retrievers were included in the present study to collect blood and feces samples for measurements. The fecal microbiome and plasma metabolome were determined using 16S rRNA amplicon sequencing and liquid chromatography-mass spectrometry, respectively.ResultsResults showed that the alanine aminotransferase activity and total bilirubin concentration, which have been measured using serum biochemistry analysis, were higher in the Obe group than in the Ctrl group (p < 0.05). Moreover, there was a significant difference in gut microbiota composition between the two groups (p < 0.05). The phyla Proteobacteria, Fusobacteriota, and Bacteroidota as well as genera Fusobacterium, Prevotella, Faecalibacterium, Escherichia-Shigell, and Alloprevotella were more abundant, while phylum Firmicutes and genera Peptoclostridium, Blautia, Turicibacter, Allobaculum, and Erysipelatoclostridium were less abundant in the Obe group compared to the Ctrl group (p < 0.05). Plasma concentrations of citrulline and 11-dehydrocorticosterone were significantly higher in the Obe group than those in the Ctrl group (p < 0.05). Close correlations between serum biochemistry parameters, gut microbiome, and plasma metabolites were observed in the current study.ConclusionThe obesity-induced shifts in serum biochemistry indexes, gut microbiota, and plasma metabolites profiles suggest that obese Golden Retrievers exhibit a different microbiome and metabolome than non-obese ones, and the certain metabolites like citrulline and 11-dehydrocorticosterone could be considered as potential biomarkers to recognize obese Golden Retrievers.